Hubungan Gaya Kepemimpinan Transformasional terhadap Kepuasan Kerja Kasryawan di PT. Kreasi Lutvi Sejahtera - Sibarani, Adinda Azima Riskiya; Lestari, Anisa Ayu; Rizki, Aprida Aulia; Ramadhani, Lutfiah; Vovo, Rahmi; Afrianda, Silvina Mutia; Wasiyem, Wasiyem (Universitas Batanghari, 2024)
This research was conducted on employees of PT Kreasi Lutvi Sejahtera. The purpose of this research is to determine the effect of transformational leadership style on employee job satisfaction at PT Kreasi Lutvi Sejahtera. The research used in this research is quantitative methods with data collection techniques through questionnaires with the population in this study being employees at PT Kreasi Lutvi Sejahtera using a sample of 37 employee at PT Kreasi Lutvi Sejahtera. The analytical tool used is the Correlation Test. The results of the analysis show that the transformational leadership style has a positive and significant influence on job satisfaction. This shows that the higher the level of Job Satisfaction expected by employees will influence the increase in Employee Performance